Tropomyosin and NEDD9 adapter roll to cell invasion by L. monocytogenes - Núñez-Montero, Kattia (2014)
Listeria monocytogenes is an animal and human pathogen that it is able to invade the intracellular space due to the interaction between bacterial surface proteins and host cell receptors, activating signaling cascades that promote pathogen internalization. Gene expression silencing in mammalian cells by transfection of small interfering RNAs (siRNA) has recently allowed the implication of novel molecular effectors to the internalization process of different intracellular pathogens in eukaryotic cells. The present work takes advantage of this technique to determine to potential contribution of tropomyosin (TPM) and the adaptor protein NEDD9 to cell invasion by L. monocytogenes, as well as Salmonella typhimurium and an Escherichia coli strain that expresses the invasin from Yersinia pseudotuberculosis. Using gentamicin invasion assays, it is shown that only TPM expression silencing reduces significantly the entry in HeLa cells of the three investigated bacterial pathogens. Fluorescence microscopy demonstrates that TPM and NEDD9 silencing affects differently HeLa cell morphology and the distribution of actin filaments. These results suggest that TPM may modulate the entry of bacterial pathogens by modifying the reorganization properties of the plasma membrane which are dependent on the actin cytoskeleton, and that these properties differ from those affected by NEDD9.